2020
DOI: 10.1016/j.isci.2020.101839
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Receptors and Entry Genes Are Expressed in the Human Olfactory Neuroepithelium and Brain

Abstract: Reports indicate an association between COVID-19 and anosmia, as well as the presence of SARS-CoV-2 virions in the olfactory bulb. To test whether the olfactory neuroepithelium may represent a target of the virus, we generated RNAseq libraries from human olfactory neuroepithelia, in which we found substantial expression of the genes coding for the virus receptor angiotensin-converting enzyme-2 (ACE2) and for the virus internalization enhancer TMPRSS2. We analyzed a human olfactory single-cell RNA-seq dataset a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
181
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(216 citation statements)
references
References 79 publications
12
181
2
4
Order By: Relevance
“…Both proteins are mainly expressed in the upper part of the respiratory tract ( Hou et al, 2020 ) and the highest density of these proteins is found in the olfactory epithelium. Sustentacular cells express most of ACE2 and TMPRSS2 and these proteins are absent from OSN ( Bilinska et al, 2020 ; Fodoulian et al, 2020 ). Both are also expressed to a lesser extent in Bowman’s gland, microvillar cells and basal stem cells ( Brann et al, 2020 ).…”
Section: Sars-cov-2 and Anosmia: Cellular Tropism In Olfactory Epithementioning
confidence: 99%
“…Both proteins are mainly expressed in the upper part of the respiratory tract ( Hou et al, 2020 ) and the highest density of these proteins is found in the olfactory epithelium. Sustentacular cells express most of ACE2 and TMPRSS2 and these proteins are absent from OSN ( Bilinska et al, 2020 ; Fodoulian et al, 2020 ). Both are also expressed to a lesser extent in Bowman’s gland, microvillar cells and basal stem cells ( Brann et al, 2020 ).…”
Section: Sars-cov-2 and Anosmia: Cellular Tropism In Olfactory Epithementioning
confidence: 99%
“…1b). Ace2 is strongly expressed in a specific area of the main olfactory epithelium (MOE), the dorsal part (MOED) which is directly exposed to the environment and specialized in sensing volatile chemical cues 14,15 . Moreover, we observed a previously unreported expression of Ace2, in the most rostral sensory subsystem, the Grueneberg ganglion (GG), mostly implicated in volatile danger cues detection [34][35][36] and in the circumvallate taste papilla (CV) involved in water-soluble tastant perception 29 .…”
Section: Sars-mentioning
confidence: 99%
“…Selected slices were then blocked for 3 h at room temperature in a PBS solution containing 5% normal donkey serum (NDS; Jackson ImmunoResearch) and 1% of non-ionic detergent (Triton ® X-100; Fluka). A double and indirect immunostaining approach using specific primary antibodies was then used to simultaneously localize ACE2 expression with other marker proteins 14,15 . The primary antibodies used were directed against ACE2 (Goat anti-ACE2; PA5-47488; Invitrogen; (which was not certified by peer review) is the author/funder.…”
Section: Chemosensory Epithelia Isolationmentioning
confidence: 99%
“…Briefly, the pathogenesis of the olfactory dysfunctions can be explained by two theories of direct viral cytopathy and systemic inflammatory cascade of events. According to recent studies, SARS-CoV-2 may affect directly the olfactory epithelium through perturbation of supporting cells which maintain the integrity of the olfactory sensory neurons and express ACE2 protein and cell surface protease TMPRSS2 which are both necessary for the virus entry into the target cells (Brann et al, 2020; Fodoulian et al, 2020). However, systematic studies on the histopathology of the olfactory epithelium in patients with COVID-19 are lacking (Deshmukh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%